2019
DOI: 10.1097/rnj.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Nurses’ Knowledge, Attitudes, and Behaviors for Preventing Urinary Tract Infections From Intermittent Catheterization

Abstract: The survey assists with identifying knowledge gaps, customizing education, and changing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…were not applied in their practice and when they had a question, they usually asked the senior nurses, rather than searched or used evidence-based measures. (Andrea et al 2020;Dawa et al, 2019;Hernandez et al, 2019).…”
Section: Undesirable Practices On Cauti's Prevention and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…were not applied in their practice and when they had a question, they usually asked the senior nurses, rather than searched or used evidence-based measures. (Andrea et al 2020;Dawa et al, 2019;Hernandez et al, 2019).…”
Section: Undesirable Practices On Cauti's Prevention and Managementmentioning
confidence: 99%
“…Heavy workload (Ivy et al, 2021) Leadership (Andrea Niederhauser et al 2020;Andrea et al, 2019;Fakih et al, 2013) Understaffing (Jane, 1997) Positive attitude (Dawa et al, 2019;Ivy et al, 2021;Andrea et al, 2019) Lack of supervision (Jane, 1997) Betterr education (Anns et al, 2020;Manisha et al, 2015;Ndomba et al, 2008;Kelly, 2020;Niederhauser et al, 2019;Drekonja et al, 2009;Viswanathan et al, 2015;Dawa et al, 2019;Shaver et al, 2018;Hernandez et al, 2019) Lack of attention to guidelines (Andrea Niederhauser et al 2020;Ivy et al, 2021) Teamwork (Andrea Niederhauser et al 2020;Andrea et al, 2019;Viswanathan et al, 2015;Dawa et al, 2019;Shaver et al, 2018;Hernandez et al, 2019;Mary et al, 2015) Lack of knowledge (Kose et al, 2016;Opina & Oducado, 2014;Shah et al, 2017) Technique training and information technology support (Balu et al, 2021;Ivy et al, 2021;Mary et al, 2015;Shaver et al, 2018) Physician variability in IUC practice by diagnosis (Mary et al, 2015) Advocacy for nurse-driven protocol (Andrea Niederhauser et al 2020;Conner, 2013) Nursing variability in IUC placement technique (Mary et al, 201...…”
Section: Barriers Facilitatorsmentioning
confidence: 99%
“…Most of the studies were reported from India (6 studies) 26,[31][32][33][34][35] : followed by United States (3 studies), [36][37][38] Ethiopia (3 studies), 2,39,40 Iraq…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were reported from India (6 studies) 26,31–35 : followed by United States (3 studies), 36–38 Ethiopia (3 studies), 2,39,40 Iraq (2 studies) 41,42 and single study from Pakistan, 43 Saudi Arabia, 44 Yeman, 12 Solvakia, 45 Nepal 46 and Malaysia 47 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation